Spatial distribution, abundance and infestation rate of freshwater intermediate host snails in Lake Kivu, DR Congo side - Bagalwa, Jean-Jacques M.; Batumike, Pierre C.; Ndegeyi, Bertin K.; Bahizire, Jean-Louis K. (European Scientific Journal, ESJ, 2024)
Molluscs play an important role in public and veterinary health, making the continuous study of their distribution essential. The main goal of this investigation was to examine the distribution of freshwater molluscs in Lake Kivu, located on the DR Congo side. Semi-quantitative surveys conducted from January to December 2019 focused on selected sites within the lake, covering both the dry and wet seasons. Snails in the littoral zone of Lake Kivu were collected using a plankton net and pliers. The physicochemical parameters of the water at each site were measured using standard water quality analysis methods. The collected snails were morphologically identified using various identification keys. Biomphalaria species were analyzed (cercariometry) for trematode infestation. A total of 1,331 snails belonging to seven genera and 18 species were recorded during the study. The relative abundance of the recorded snail species was as follows: Biomphalaria pfeifferi (49.6%), Biomphalaria smithi (16.6%), Gabbiella spirilosa (10.6%), Bulinus truncatus (10.1%), Lymnaea natalensis (6.5%), Helisoma duryi (1.5%), Pila ovata and Tomichia ventricosa (0.8% each), Melanoides tuberculata (1.7%), Lymnaea columella and Tomichia hendrexyx (0.9% each), Bulinus forskalii and Tomichia zwellandanensis (0.9% each), Physa acuta (0.4%), Corbicula fluminalis (1.1%), Lymnaea palustris (0.2%), Tomichia kivuensis and Segmentorbis kempi (0.1% each). This study clarified the distribution and seasonal abundance of freshwater snails in Lake Kivu, DR Congo. Eighteen species of freshwater snails were identified during the malacological survey. The observed snail distribution provides insights into the epidemiology of trematode infections in the study area and highlights potential risks to human and animal health. The implications of these findings for controlling snail-borne trematodes are also discussed.